1987
DOI: 10.1515/cclm.1987.25.11.765
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Non-Opsonized Zymosan-Induced and Luminol-Enhanced Chemiluminescence in Whole Blood and Isolated Phagocytes

Abstract: Summary:A lumiüol-dependent non-opsonized zymosan-induced chemiluminescence method for phagocytes in small quantities of whole blood (40 ; final dilution: l : 14) is described. It was characterized with reference to cellular and humoral components, and also applied to isolated neutrophils, eosinophils and monocytes. Normal values for whole blood chemiluminescence and for neutrophils, eosinophils and monocytes are presented. From the chemiluminescence characteristic of distinct phagocytes and their frequency di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0
4

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 18 publications
3
39
0
4
Order By: Relevance
“…The enhanced phagocytosis could be due to increased receptor expression (complement 3b-, Fc-receptor) on the surface of myeloperoxidase deficient granulocytes, which may contribute to the complex pattern of luminol and lucigenin chemiluminescence (29,30). In myeloperoxidase deficient cells, additional numbers of these receptors may be more easily translocated from an intracellular pool to the cell membrane during stimulation (31).…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced phagocytosis could be due to increased receptor expression (complement 3b-, Fc-receptor) on the surface of myeloperoxidase deficient granulocytes, which may contribute to the complex pattern of luminol and lucigenin chemiluminescence (29,30). In myeloperoxidase deficient cells, additional numbers of these receptors may be more easily translocated from an intracellular pool to the cell membrane during stimulation (31).…”
Section: Discussionmentioning
confidence: 99%
“…We have, however, recently shown that increasing the citrated plasma volume fraction while holding erythrocyte and neutrophil numbers constant results in steadily increasing peak maximum values. In addition, a shift to a higher volume fraction of citrated plasma against a lower volume fraction of erythrocytes has been shown to increase peak maximum counts (18). The decrease in opsonin-dependent (CL1), as well as in opsonin-independent (CL2) peak maximum values from isolated granulocytes does not indicate a more preferential plasma-or cell-mediated alteration.…”
Section: Discussionmentioning
confidence: 96%
“…The major chemiluminescence response of granulocytes to the particulate stimulatory agent, zymosan, is brought about by the interaction of the complement receptor type 3 of granulocytes with the plasma-derived zymosan-coated cleavage products of complement fraction three, iC3b and to a minor degree C3b. In the absence of plasma this receptor also mediates a chemiluminescence response from the interaction with the zymosan polysaccharide component, glucan (18).…”
Section: Chemiluminescence Of Whole Blood and Isolated Granulocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Luminol-enhanced CL assay is a very sensitive and reliable tool for determining the opsonic activity of serum (2,(9)(10)(11)16 both serum and blister fluid could be corrected in vitro by adding normal serum to the burn patient's serum (4,6). It was reported that treatment with FFP as adjunctive therapy for massive burns was more effective for maintaining the serum opsonins than that of plasma protein derivative (this product is essentially devoid of IgG and functional complement) (1).…”
mentioning
confidence: 99%